In vitro toxicity assessment of paints with antimicrobial properties - a comparative study - Machado-Querido, M. (2021)
In this work, the in vitro cytotoxicity of self-disinfecting wall paints containing antimicrobial substances was assessed, using skin and lung cell lines.